2-(2-Phenylethyl)chromone derivatives: Promising α-glucosidase inhibitors in agarwood from Aquilaria filaria. (January 2021) - Mi, Cheng-neng; Yuan, Jing-zhe; Zhu, Man-man; Yang, Li; Wei, Yan-mei; Wang, Hao; Long, Wen-xing; Mei, Wen-li; Dai, Hao-fu
Abstract: Twelve undescribed 2-(2-phenylethyl)chromone derivatives, including one pair of enantiomers, together with eleven known ones, were isolated from the EtOAc extract of agarwood originating from Aquilaria filaria . All structures were elucidated by spectroscopic (NMR, UV, IR, MS) methods and compared with reported data in literatures. Twenty-one compounds were assessed for α -glucosidase inhibitory activity, which showed inhibition of α -glucosidase with IC50 values ranging between 7.8 ± 0.3 to 137.7 ± 3.0 μM (Acarbose, 743.4 ± 3.3 μM; Genistein, 8.3 ± 0.1 μM). Our results expanded the structural diversity of 2-(2-phenylethyl)chromones from agarwood, and revealed the potential of 2-(2-phenylethyl)chromones as α -glucosidase inhibitors. Graphical abstract: Image 1 Highlights: Twelve undescribed 2-(2-phenylethyl)chromones were found from agarwood of Aquilria filaria. 8′-OH and 8-methylsulfinyl substituted chromones are the first examples reported from agarwood. Twenty-one compounds showed inhibitory activity against α- glucosidase. The inhibition kinetic study revealed chromones as mixed type inhibitor of α -glucosidase.